PEMERINTAHAN DESA: “UNIT PEMERINTAHAN PALSU” DALAM SISTEM ADMINISTRASI NEGARA REPUBLIK INDONESIA (Kasus Desa Jabon Mekar, Parung, Kabupaten Bogor) - Hanif Nurcholis (Jurnal Politica, 2014)
Rural government is the lowest level of Indonesian administrative system under regency or city and province. Itsexistence under the Dutch colonial era is admitted as part of the colonial government’s recognition to customary law. There was, however, a new dynamic in post-independence era, during which under Law No. 19/1965, its role was diminished, and after the enactment of law No. 5/1979, its existence has been admitted again. Using its public administration point of analysis, this paper generates question whether or not the rural government similar with local state government, local self government or non-government organization. To answer this question, the writer conducted field research in Jabon Mekar, applying observation method, combining with in-depth interview, document studies. Data was also gathered from FGD, and further analyzed by using descriptive-qualitative method. From this empirical research, the writer concludes that rural government could be considered as a pseudo-government body.